Applicability of Andean sanitary standards in the trade of terrestrial animals and their products, in relation to diseases exotic to the subregion. Period 2010 - 2017 - Guerrero Cespedes, Rosa (2021)
The purpose of the study was to evaluate the applicability of the Andean health standards related to exotic diseases of importance in the Andean subregion in the trade of animals and their products. From the analysis was quantified that the largest volume of imports was poultry, pigs and cattle, similar to Europe with commercial movements of live animals. The Andean regulations had variable coverage. From the imports of animals and their products made by the Member Countries of the Andean Community (Bolivia, Colombia, Ecuador and Peru), the main countries which reported exotic diseases were Belgium, China, United States of America, Canada, Chile and Italy; and the customs risk tariff were identified with a total for cattle of 15 goods, equids 2 goods, sheep-goats 6 goods, pigs 6 goods and birds 15 goods. The study showed 100% compliance with the Andean standards for bees, lagomorphs, and their products, 62.5% for cattle, 59.5% for birds, 80.6% for sheep - goats, 76.9% for pigs, and 50% for equids. This implies that risk products were imported and the Member Countries did not comply with regulations; leaving open the possibility of entry of exotic agents. The results suggested that the Member Countries and the General Secretariat of the Andean Community should establish a review and adjustments of requirements related to exotic diseases and customs tariffs, to ensure that Andean regulation are observed, in safeguarding public and animal health of the subregion.